(untitled) - Foner, Eric (New York, 2005)
Offering instructors and students a lower-price alternative to the regular editions of our leading textbooks, the Norton Seagulls feature inviting, clear designs that focus student attention on the texts themselves. These compact books are portable, affordable, and authoritative. The Seagull Edition of Eric Foner's Give Me Liberty! An American History contains the complete text of the regular edition. Acclaimed by instructors and students and adopted at hundreds of colleges and universities across the country, Give Me Liberty! provides a fresh and effective approach to the survey. Its single-author narrative gives students a clear, coherent introduction to American history. The theme of American freedom enriches the narrative, integrates the book's coverage of social and political history, and motivates the study of history by alerting students to how much is at stake in having a knowledge of our past. The book is supported by the same full array of print and electronic ancillaries as the regular edition.
Keywords: Democracy,Liberty,Hoa Kỳ,Chế độ dân chủ,Quyền tự do; History,History,Lịch sử,Lịch sử,Lịch sử; United States,Hoa Kỳ